Marriage, Divorce and Reservation Wages - Roberto Bonilla; Francis Kiraly; Miguel Ángel Malo; Fernando Pinto Hernández (CESifo GmbH, 2024)
We present an equilibrium model of inter-linked frictional labour and marriage markets. In the marital market, men and women are involved in random sequential search for a partner. Men are seen as breadwinners in the family, and therefore in the labour market unemployed men carry out a constrained sequential search for jobs. We establish that when divorce (initiated by women) is an option, in an equilibrium with male marriage premium married men have a higher reservation wage than single men. This result holds with both exogenous and endogenous wage distributions, where the latter scenario implies firms discriminate by marital status. Ironically, at birth men are better off because divorce is possible: the wage posting mechanism allows them to extract the utility loss from a potential future divorce in the form of higher reservation wages, and thus better wage offer distributions. We successfully test our results using German data.
Keywords: D83; J12; J16; J31; 330; frictional labour markets; frictional marriage markets; reservation wages